Three theses on the mediatization of politics: evolutionist, intended, or imagined transformation?. Issue 3 (3rd July 2019) - Kissas, Angelos
ABSTRACT: This article discusses the mediatization of politics and its theorization as a process of transformation in the making of (political) meaning through three different theses, presented as evolutionist, intended, and imagined transformation. These theses differ from each other not as much on what they describe as meaning-making transformation – the personalization, conversationalization, and dramatization of politics – as on what they consider to be the causes, extent, and consequences of this transformation. By examining their differences, the article argues that mediatization cannot be fully explained with reference either to a single-universal media logic (as in the thesis of evolutionist transformation) or actor-perceived media logics (as in the thesis of intended transformation). It is seen (in the thesis of imagined transformation), instead, as being catalyzed by the imaginary of media omnipresence, the overwhelming sense that media are everywhere, and therefore potential media effects must be anticipated, which intensifies the fusion of public with private spheres of political life. At the same time, this private-public fusion takes place through existing, institutionalized practices of media performativity, such as the performativity of charisma (personalization), ordinariness (conversationalization) and spectacle (dramatization), bearing implications for the exercise of power and democratic practice in our societies.